The Quebec Pregnancy Cohort--prevalence of medication use during gestation and pregnancy outcomes. - Anick Bérard; Odile Sheehy (PLoS ONE)
Purpose We evaluated the potential and the validity of the Quebec Pregnancy Cohort (QPC) as a research tool in perinatal pharmacoepidemiology. Methods The QPC was built by linking four administrative databases: RAMQ (medical and pharmaceutical data), Med-Echo (hospitalizations), ISQ (births/deaths), and MELS (Ministry of Education data). A self-administered questionnaire was sent to a random sample of women to collect lifestyle information. The QPC includes data on all pregnancies of women covered by the Quebec provincial prescription drug insurance between 1998 and 2008. Date of entry in the QPC is the first day of pregnancy, and women are followed during and after pregnancy; children are followed after birth up until 2009. The prevalence of prescribed medications before, during and after pregnancy was compared between time-window. Pregnancy outcomes were also estimated among pregnancies ending with a live born infant. Results The QPC included 289,688 pregnancies of 186,165 women. Among them, 167,398 ended with a delivery representing 19.4% of all deliveries occurring in the Province of Quebec between 1998-2009. The total frequency of abortions was 35.9% in the QPC comparable to the 36.4% observed in the Province of Quebec. The prevalence of prescribed medication use was 74.6%, 59.0%, and 79.6% before, during and after pregnancy, respectively. Although there was a statistically significant decrease in the proportion of use once the pregnancy was diagnosed (p<.01), post-pregnancy prescribed medication use returned above the pre-pregnancy level. The prevalence of pregnancy outcomes found in the QPC were similar to those observed in the Province of Quebec. Conclusion The QPC is an excellent tool for the study of the risk and benefit of drug use during the perinatal period. This cohort has the advantage of including a validated date of beginning of pregnancy giving the possibility of assigning the exact gestational age at the time of maternal exposure.